2019
DOI: 10.3390/antiox8010014
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Novel Application of Hydrodynamic Voltammetry to the Study of Superoxide Radical Scavenging by Natural Phenolic Antioxidants

Abstract: The reactions of antioxidants with superoxide radical were studied by cyclic voltammetry (CV)—and hydrodynamic voltammetry at a rotating ring-disk electrode (RRDE). In both methods, the superoxide is generated in solution from dissolved oxygen and then measured after being allowed to react with the antioxidant being studied. Both methods detected and measured the radical scavenging but the RRDE was able to give detailed insight into the antioxidant behavior. Three flavonoids, chrysin, quercetin and eriodictyol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 31 publications
1
52
3
Order By: Relevance
“…Emodin was added in aliquots and the more the antioxidant was added, the less superoxide radical was detected at the ring electrode. In contrast with a previous study [22], there was an increase of current in the area −0.2-0.4 V. Therefore, a specific voltammogram for emodin, without O2 in the voltaic cell This demonstrates that the π-π approach is able to sequester superoxide.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Emodin was added in aliquots and the more the antioxidant was added, the less superoxide radical was detected at the ring electrode. In contrast with a previous study [22], there was an increase of current in the area −0.2-0.4 V. Therefore, a specific voltammogram for emodin, without O2 in the voltaic cell This demonstrates that the π-π approach is able to sequester superoxide.…”
Section: Discussioncontrasting
confidence: 86%
“…Emodin was added in aliquots and the more the antioxidant was added, the less superoxide radical was detected at the ring electrode. In contrast with a previous study [22], there was an increase of current in the area −0.2-0.4 V. Therefore, a specific voltammogram for emodin, without O2 in the voltaic cell (e.g., purged with N2), was performed (Figure 11) and confirmed emodin reduction in the same area. Figure 10 shows the RRDE voltammograms obtained after addition of aliquots to the voltaic cell containing DMSO bubbled with oxygen.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Despite hydrogen peroxide, O 2 −• has the potential to be detected (since it has longer time of life). However, most of its detection methods are considered as indirect extents since most of them focus on measuring a product generated by superoxide consumption or production as the criteria of superoxide presence or its concertation [214] . The most notable point about the indirect measurements is that it is better to validate the results with other methods in order to have reliable recorded data.…”
Section: The Level Of Os and Related Compoundsmentioning
confidence: 99%
“…Another study of the superoxide scavenging activity of catechins found that, while almost all flavonoids examined were able to scavenge superoxide radical anions, the flavan-3-ols with a dihydroxy substituted system had much lower scavenging activity than either flavan-3-ols with trihydroxy substituted rings (either gallate or pyrogallol) or flavones with dihydroxy substituted B-rings [ 84 ]. The conjugated system of flavones such as quercetin would be expected to follow the same mechanism as the catechins and be able to both generate and scavenge superoxide ions in aqueous solutions, just like the catechins [ 85 ].…”
Section: Chemistry Of Flavonoids In Aqueous Solutionsmentioning
confidence: 99%